EXPLORING TUTORS’ STRATEGIES IN TEACHING SPEAKING AT PPB IAIN SYEKH NURJATI CIREBON - Umar Umar (Universitas PGRI Palembang, 2024)
This study, which includes an English tutor and 30 students in the third semester of the class PPB IAIN Syekh Nurjati Cirebon, aims to portray tutors’ tactics in teaching speaking to PPB IAIN Syekh Nurjati Cirebon and recognize the effects of strategies used by the English tutors. To determine the speaking instruction methodologies, interviews, and classroom observations were undertaken as part of the data collection. The outcome showed that the tutors’ methods included drills, role-plays, speaking lines, and discussions. As a result of the teacher's speaking techniques, pupils get more engaged in their studies, develop more optimistic outlooks, and become more motivated. Almost all of the students prefer the speaking lines as the method of teaching speaking among the three tactics used by the teacher because they believe it can enhance their speaking skills, increase their desire to talk and make the teaching-learning process more enjoyable.